Tooth morphometry and the pattern of palatal rugae among monozygotic and dizygotic twins in India - Swagatika Panda; Alkananda Sahoo; Neeta Mohanty; Sujit R Sahoo; Ramanarayanan Subramaniam (Wolters Kluwer Medknow Publications, 2017)
Introduction: A stronger correlation of physical traits among monozygotic (MZ) twins than dizygotic (DZ) twins indicates predominant contribution by genetic factors than environmental factors. Exploring the degree of resemblance in tooth morphometry and the pattern of rugae among twins shall aid in forensic identification. Aim and Objective: To find out the degree of correlation in tooth morphometry and the palatal rugae pattern among MZ and DZ twins. Materials and Methods: The maximum coronal mesiodistal and buccolingual dimensions of the maxillary teeth excluding the second and third molars in 21 pairs of MZ and 12 pairs of DZ twins along with a MZ triplet were recorded using digital calipers calibrated to 0.01 mm. The dimensions of the teeth based on the number, shape, size, and the unification palatal rugae pattern among twin pairs were analyzed and recorded. Results: Our results suggest a stronger correlation of tooth dimension among MZ than DZ twins, which differs for individual maxillary tooth. There may be a separate set of genes responsible for controlling the mesiodistal and buccolingual tooth dimensions. The maxillary canine and maxillary premolars do show the least amount of genetic variability. The results in our study provide remarkable evidence regarding the existence of mirror imaging in tooth dimension as well as the number and shape of the palatal rugae. Conclusion: This first of its kind study in the Indian population suggests a remarkable similarity with regard to the tooth's size and uniqueness of the palatal rugae pattern among MZ and DZ twins, which suggests their strong inheritability potential. This may be useful as additional tools for zygosity determination along with other dental traits. The significant evidence of mirror imaging of tooth dimension and rugae shall definitely contribute to the concept of development of human body.